(untitled) (Research, Society and Development, 2020)
Visceral Leishmaniasis (VL) as an antrophozoonose of high lethality it can cause death in 90% of the cases which are not adequately treated. The disease is characterized by the hepatosplenomegaly and fever. VL is caused by protozoan from the species of Leishmania infantum chagasi and it is conveyed through phlebotomine. In our study we did a epidemiological analysis of notified cases in State of Piauí, we did this using data from National Grave Notified System, in the period from 2009 to 2018. The quantity of cases of VL in Piauí is exactly at 2 101, in an incidence of 6.6 cases per one hundred million (6.6/100 000) inhabitants. Cities that shows the highest rates of cases are: Avelino Lopes Town (28.09), Miguel Alves (26.98) and Pavussu (26.82). The media age of people who are most infected are from 0 to 4 years old (27.13/100 000 inhabitants. The most affected gender are men in the rate of 68% of VL total cases. The lethality rate was 6.62%. According to the our researching data a VL in Piauí State shows urban character. We detach the quantity of cases in Teresina Capital State City because it has a bigger population in comparison to other cities. VL is more prevalent where living conditions are precarious. Based on our analysis it is possible to point out groups that present high risks to VL and data analyzed also show what make them more vulnerable to acquire the illness. This way it is possible to control disease into those groups and effectively to develop a guiding control on them. Doing this, similar examples of effective control of Viral Leishmaniasis can be applied in all along America continent, if they have the same epidemiological characteristics.